Navigating Biological Health Hazards in Dentistry: Understanding Risks And Ensuring Safety (Indian Journal of Public Health Research & Development, 2025)
Occupational hazards can be defined as a risk to a person usually arising out of employment. It can also refer to a work, material, substance, process, or situation that predisposes or itself causes accidents or diseases at workplace. The history of occupational hazard awareness can be traced back to the 18th century when “Bernadine Ramazzini”, who is referred to as the “Father of occupational medicine”, recognized the role of occupation in the dynamics of health and disease. Dental practice encompasses a diverse range of services to patients of all ages, aimed at preventing, diagnosing, and treating oral diseases and conditions. However, the practice of dentistry also entails exposure to various biological hazards that can pose risks to the health and safety of dental personnel. Therefore, the present review will be an attempt to provide an overview of the different categories of biological hazards faced by dental professionals by examining the various sources, potential health effects, and strategies for mitigation.
Keywords: Biological hazard, Dentistry, Occupational hazard, Cross-infection, Risk